POTENSI EFEKTIVITAS PUPUK BERSUBSIDI DALAM PENINGKATAN PEREKONOMIAN MASYARAKAT TANI - sah ikhlas (Journal Of Islamic Economics And Finance, 2022)
Jetak Kidul is a village geographically surrounded by agriculture, especially rice farming. So it’s not a taboo if most of the people there still work as farming communities and depend on them for their livelihoods. However, in cultivating agriculture, the farming community of Jetak Kidul village is often constrained by costs due to their relatively weak capital strength. And to try to solve the problem, the order issued a policy of subsidized fertilizer which is expected to help farming communities. Therefore, the author will conduct a study which aims to analyze the potential effectiveness of the level of satisfaction of the farming community with the subsidized fertilizer program and find out how the effect of the subsidized fertilizer program on the economy of the farming community in the village of Jetak Kidul. The result of this research is that subsidized pupup has the potential for effectiveness in improving the community’s economy. As long as the indicators used in the study are all met.